Take my wife-- : 535 jokes, riddles, quips, quotes, and wisecracks about love, marriage, and the battle of the sexes /: 535 jokes, riddles, quips, quotes, and wisecracks about love, marriage, and the battle of the sexes. (©2008) - Unknown
No abstract available